2015
DOI: 10.1038/cdd.2014.231
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of H2A deubiquitinase 2A-DUB/Mysm1 and the p19ARF/p53 axis in hematopoiesis, early T-cell development and tissue differentiation

Abstract: Monoubiquitination of core histone 2A (H2A-K119u) has a critical role in gene regulation in hematopoietic differentiation and other developmental processes. To explore the interplay of histone H2A deubiquitinase Myb-like SWIRM and MPN domain containing1 (2A-DUB/Mysm1) with the p53 axis in the sequential differentiation of mature lymphocytes from progenitors, we systematically analyzed hematopoiesis and early T-cell development using Mysm1−/− and p53−/−Mysm1−/− mice. Mysm1−/− thymi were severely hypoplastic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(114 citation statements)
references
References 70 publications
7
107
0
Order By: Relevance
“…Previous studies detected an enhanced thymic p53 expression in Mysm1 −/− mice, 35 which implies that Mysm1 −/− affects the thymus in addition to reducing input of CLPs from BM. Hence, we directly analyzed Mysm1 −/− thymocytes for IRF2 and IRF8 expression.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies detected an enhanced thymic p53 expression in Mysm1 −/− mice, 35 which implies that Mysm1 −/− affects the thymus in addition to reducing input of CLPs from BM. Hence, we directly analyzed Mysm1 −/− thymocytes for IRF2 and IRF8 expression.…”
Section: Resultsmentioning
confidence: 93%
“…Belle et al 34 and Gatzka et al 35 independently generated Mysm1 −/− p53 −/− mice that largely restored Mysm1 deficiency-associated defects. Moreover, Gatzka et al 35 revealed that increased p53 levels in Mysm1 −/− mice may result from the upregulation of p19 ARF that stabilizes p53 by blocking nucleo-cytoplasmic shuttling of Mdm2. 35 However, Mysm1 is a H2ADUB that generally functions as a transcription activator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our groups as well as other independent groups have observed an essential role of MYSM1 for bone marrow hematopoietic development and lymphocyte generation [1521]. In spite of these observations, knowledge of the biological functions of MYSM1 remains limited, and its function in B1a cell proliferation had not been investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Rag1 −/− or Cd3 γ −/− mice), which fail β-selection but can by-pass this checkpoint when Trp53 (p53) is deleted or mutated(6, 7). Stabilization of p53 prevents B and T cell development beyond the pre-antigen receptor checkpoints, as evidenced in mice lacking genes that directly regulate p53 at the transcriptional (WIP1(8, 9), MYSM1(10)), post-transcriptional (CNOT(11)), translational (RPL22(12, 13), MIZ1(14, 15)), or post-translational (YY1(1618), BCL11A(19), NIR(20)) levels. Remarkably, B and T cell maturation are substantially restored in these mice upon deletion of p53.…”
Section: Introductionmentioning
confidence: 99%